Physics for kids : : 49 easy experiments with optics - Wood, Robert W. (TAB Books, 1990)
Provides instructions for forty-nine experiments in optics, including "How to Bend Light Waves with Your Fingers," "How to Make a Prism," and "How to Build a Refracting Telescope."